Avaliação da atividade autofágica nos processos neurodegenerativos da via nigroestriatal em modelo experimental da doença de Parkinson - Santos, Edson de Rezende (2022)
Parkinson's disease (PD) is the most prevalent neurodegenerative movement disorder. It is characterized by neurodegeneration in the nigrostriatal pathway [substantia nigra (pars compacta – SNpc – and pars reticulata – SNpr) and striatum] and the presence of aggregated α-synuclein (α-syn), which results in motor and nonmotor symptoms. Disturbances in autophagy, a natural process of cleaning and recycling intracellular material, seem to play a relevant role in the development or progression of the disease or both. This work assessed the participation of autophagy in the nigrostriatal pathway of parkinsonian animals. Sixty-four Wistar rats were used and randomly divided into four groups (n = 16): 1) control (CTRL); 2) RES 0.1; 3) RES 0.2, and 4) RES 0.5. The RES groups were separated using the following doses: 0.1, 0.2, and 0.5 mg/kg, respectively. Fifteen injections of RES were administered, one every 48 hours, subcutaneously. During the entire experiment, behavioral tests were performed for voluntary motor assessment (catalepsy, every 48h); and involuntary (oral movements (OM) on the days 10, 20, and 30; 48h after 5th, 10th, and 15th injections, respectively) and non-motor (body weight assessment, every four days). Forty-eight hours after the 15th injection, twenty-four animals (six from each group) were perfused, and the brains were submitted to immunohistochemistry for tyrosine hydroxylase (TH – SNpc/striatum) and α-syn (SNpr/striatum). Forty animals (ten from each group) were decapitated, and the brains were removed and dissected to obtain the striatum and substantia nigra (SN). These structures were processed and submitted to the western blot technique for LC3-II, P62/SQTSM1, PARK7/DJ-1, and caspase-3. In catalepsy, the motor symptoms were dose-dependent; the higher the dose of RES, the earlier the motor deficits started. The RES 0.5 group became cataleptic after the 3rd injection (p = 0.02), while in the RES 0.2 and RES 0.1 groups, catatonia started 48h after the 5th and 6th injections (p < 0. 0001), respectively. The OM test evaluated the following parameters: chewing movement and resting tremor time. In general, there was a statistically significant increase (p < 0.05) of these parameters in the RES groups on all evaluation days. A reduction in immunoreactive TH cells was observed in the SN (RES 0.1, p = 0.019; RES 0.2, p = 0.006; RES 0.5, p = 0.0006) and striatum (RES 0.1, p = 0.001; RES 0.2, p = 0.004; RES 0.5, p = 0.007). In SNpr and striatum, there was an increase in α-syn immunoreactive neurons in all RES groups (p > 0.05). In SN, an increase in P62 levels was observed in all RES groups (p = 0.001) and PARK7 only in the RES 0.5 group (p < 0.0001). In the striatum, there was an increase in LC3-II in the RES 0.2 (p = 0.010) and RES 0.5 (p = 0.043), PARK7 and caspase-3 in the RES 0.5 group (p = 0.038; p = 0.016, respectively). These data suggest that the impairment of the autophagic pathway may directly contribute to neurodegeneration in the animal model of PD in the prodromal stages.